2008
DOI: 10.1159/000117794
|View full text |Cite
|
Sign up to set email alerts
|

Tension-Free Vaginal Tape and Autologous Rectus Fascia Pubovaginal Sling for the Treatment of Urinary Stress Incontinence: A Medium-Term Follow-Up

Abstract: Objectives: To compare two different procedures, tension-free vaginal tape (TVT) and autologous rectus fascia sling, according to their medium-term subjective and objective outcomes and satisfaction rates in the treatment of urinary stress incontinence in women. Subjects and Methods: One hundred women with type II urinary stress incontinence were randomized to be treated with either TVT or autologous rectus fascia sling. They were evaluated by means of a cough-induced stress test, 1-hour pad test, Incontinence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…This value is consistent with the literature ones, 83% to 94% 8,[14][15][16] . Table 2 -Table 2 -Table 2 -Table 2 -Table 2 Table 3 -Table 3 -Table 3 -Table 3 - Table 3 Analysis of variance with summary measures (General).…”
Section: Results Results Results Resultssupporting
confidence: 94%
“…This value is consistent with the literature ones, 83% to 94% 8,[14][15][16] . Table 2 -Table 2 -Table 2 -Table 2 -Table 2 Table 3 -Table 3 -Table 3 -Table 3 - Table 3 Analysis of variance with summary measures (General).…”
Section: Results Results Results Resultssupporting
confidence: 94%
“…The authors concluded that Ophira and TOT procedures were comparable in terms of both objective and subjective cure rates; however the major advantage of Ophira compared to TOT was the facility of performing the procedure under local anesthesia on an ambulatory basis with less postoperative pain and intraoperative complication (Smith et al, 2011). Sharifiaghdas and Mortazavi (2008) have compared tension-free vaginal tape (TVT) with rectus facia pubovaginal sling in 61 patients (25 in the TVT and 36 in the sling group). The authors concluded that TVT and pubovaginal rectus facia sling were comparable in terms of both objective and subjective cure rate (Sharifiaghdas and Mortazavi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sharifiaghdas and Mortazavi (2008) have compared tension-free vaginal tape (TVT) with rectus facia pubovaginal sling in 61 patients (25 in the TVT and 36 in the sling group). The authors concluded that TVT and pubovaginal rectus facia sling were comparable in terms of both objective and subjective cure rate (Sharifiaghdas and Mortazavi, 2008). Our study showed an objective cure rate of 84.2% and 88.6% in the sling and Ophira groups respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 More recently, Sharifiaghdas et al randomized 100 women with SUI to either autologous rectus fascia PVS or tension free vaginal tape (TVT). 18 Thirty-nine percent were lost to follow-up by 1 year. Of those who reached 1 year of follow-up, the mean follow-up time for the PVS and MUS was 40 and 38.5 months, respectively.…”
Section: Commentmentioning
confidence: 99%